Electron‐Activated Tandem Mass Spectrometry Analysis of Glycosaminoglycans. Issue 4 (2nd April 2021) - Pepi, Lauren E.; Amster, I. Jonathan
Abstract: Glycosaminoglycans (GAGs) are linear polysaccharides found in a variety of organisms. GAGs contribute to biochemical pathway regulation, cell signaling, and disease progression. GAG sequence information is imperative for determining structure‐function relationships. Recent advances in electron‐activation techniques paired with high‐resolution mass spectrometry allow for full sequencing of GAG structures. Electron detachment dissociation (EDD) and negative electron transfer dissociation (NETD) are two electron‐activation methods that have been utilized for GAG characterization. Both methods produce an abundance of informative glycosidic and cross‐ring fragment ions without producing a high degree of sulfate decomposition. Here, we provide detailed protocols for using EDD and NETD to sequence GAG chains. In addition to protocols directly involving performing these MS/MS methods, protocols include sample preparation, method development, internal calibration, and data analysis. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of glycosaminoglycan samples Basic Protocol 2 : FTICR method development Basic Protocol 3 : Internal calibration with NaTFA Basic Protocol 4 : Electron Detachment Dissociation (EDD) of GAG samples Basic Protocol 5 : Negative electron transfer dissociation (NETD) of GAG samples Basic Protocol 6 : Analysis of MS/MS data